2009
DOI: 10.1186/1752-1947-3-76
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella bronchiseptica pneumonia in a man with acquired immunodeficiency syndrome: a case report

Abstract: IntroductionBordetella bronchiseptica can be a cause of virulent pneumonia in humans with impaired immune systems. Few cases have been reported in the medical literature where Bordetella bronchiseptica has been the only pathogen isolated during a course of interstitial pneumonia.Case presentationA 42-year-old African-American man with human immunodeficiency virus presented with pulmonary symptoms that mimicked Pneumocystis jiroveci pneumonia. A sputum culture grew Bordetella brochiseptica, a common respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…Bordetella bronchiseptica, an aerobic Gram-negative rod bacteria often associated with mammals, is an infrequent pathogen in immunocompromised subjects causing a variety of respiratory manifestations ranging from sinusitis tracheobronchitis, pneumonia, and septicemia. Of note, our patient did not have any history of close contact with animals [1][2][3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 85%
“…Bordetella bronchiseptica, an aerobic Gram-negative rod bacteria often associated with mammals, is an infrequent pathogen in immunocompromised subjects causing a variety of respiratory manifestations ranging from sinusitis tracheobronchitis, pneumonia, and septicemia. Of note, our patient did not have any history of close contact with animals [1][2][3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 85%
“…In humans, B. bronchiseptica infection is not common (2). If a human is infected, it is thought that this infection comes from an infected animal with B. bronchiseptica (3). Especially in the young children, in those with underlying disease and in HIV-infected individuals with suppressed immune system, B. bronchiseptica infection has appeared more frequent and severe compared to healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The patient had been in contact with a domestic dog. 9 Wernli et al described eight cases of BB that caused infection or colonization in human beings over a 15-year period. 16 Those researchers showed that seven of their patients had underlying diseases and that only three had been in contact with domestic animals.…”
Section: Reportmentioning
confidence: 99%
“…It generally occurs in patients with weak immune systems, such as AIDS patients. [6][7][8][9] Two cases of pneumonia caused by BB in HIV-positive patients at a university hospital are reported below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation